10.5k views
1 vote
Solution to problem
-2(x-3)

User JRsz
by
5.5k points

2 Answers

3 votes

Answer:

Distribute the -2

-2x+6

Make equation equal to 0

-2x+6 = 0

Then solve for x since that will be your solution

Explanation:

User Mikefrey
by
5.3k points
7 votes
Hello!

1. Distribute the -2 to both terms in the parentheses.

-2x+6

2. Set the equation equal to 0 & solve for x.

-2x+6=0

3. Subtract 6 from both sides.

-2x=-6

4. Divide both sides by -2 to solve for x.

x=3

There’s your answer, x=3! :)
User Tutankhamun
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.